Efficiency of Rubella Test Kit Produced by the Department of Medical Sciences - Warachit, Paijit; Pattamadilok, Sirima (Journal of Health Science of Thailand, 1993)
One hundred and twenty one sera were used for efficiency comparison between the rubella test kit produced by Department of Medical Sciences (Rub-HAI Kit, DMS) and the commercial kit (Rube-HIT, Behring). The qualitative determination of rubella antibodies in sera showed that the sensitivity, specificity, positive predictive value, negative predictive value and efficiency of Rub-HAI kit were 92.4%, 100%, 100%, 78.6% and 94.1%, respectively. A number of patients with recent rubella infections were also investigated, and it was found that the accuracy of test kit was comparable to that of the commercial one. In terms of the diagnostic cost, Rub-HAI kit was much lower about thirty-five times less. So the rubella test kit produced by Department of Medical Sciences is suitable and very useful for health services of the Ministry of Public Health.